High‐Resolution Optical Observations of Neutral Heating Associated With the Electrodynamics of an Auroral Arc. Issue 11 (23rd November 2019) - Price, D. J.; Whiter, D. K.; Chadney, J. M.; Lanchester, B. S.
Abstract: We present results that indicate the existence of two distinct neutral heating processes associated with a discrete auroral arc over Svalbard. Within the order of seconds, the thermospheric temperature profile displays a significant response to the arc on spatial scales smaller than 10 km. It is suggested that both heating signatures are associated with the electrodynamic system responsible for the formation of the arc. Pedersen currents produce a temperature increase of approximately 100 K, observed at altitudes between 80 and 160 kilometres, directly adjacent to the arc structure and on its poleward edge only. In contrast, field‐aligned currents produce a variable temperature increase, of approximately 50 K, which is observed within the arc itself and constrained to a narrow altitude range between 90 and 110 km. By utilizing a range of observations and new analysis methods we are able to measure the atmospheric neutral temperature profile, over auroral altitudes, at unprecedented temporal and spatial scales. The High Throughput Imaging Echelle Spectrograph records high‐resolution emission spectra of the aurora, which are then fitted with synthetic N2 spectra, generated with modeled N2 volume emission rate profiles and a library of trial temperature profiles. The N2 volume emission rate profiles are retrieved from the Southampton ionospheric model using precipitating particle energies and fluxes obtained from Auroral Structure and Kinetics and the EISCAT Svalbard Radar. The application of this technique allows us to produce a time series of neutral temperature profiles and measure the localized heating of the neutral atmosphere resulting from the electrodynamics of the arc. Key Points: Development of a new observing technique allows for the measurement of neutral temperature profiles during auroral events at an unprecedented temporal resolution A case study of a morning sector auroral arc over Svalbard reveals a region of significant Joule heating on its poleward edge Evidence of a separate Ohmic heating signature embedded within the arc and associated with strong field aligned currents